Effect of laser and light emitting diode bleaching techniques on micro-leakage of dental composite postoperatively using two different bonding systems - Shalaw S. Jawhar; Bassam K. Amin (Erbil Dental Journal)
Background and objective: Aesthetics is mostly a subjective perception that varies from individual to individual. The main objective of this study was to evaluate and compare the effects of LASER and light emitting diode bleaching techniques on the micro-leakage of composite resin restorations that were bonded with fifth and seventh adhesive bonding generations.